INTERNALISASI NILAI-NILAI TOLERANSI SEBAGAI UPAYA MENINGKATKAN INTEGRASI SOSIAL MELALUI FORUM PERSAUDARAAN BANGSA INDONESIA (FPBI) DI KOTA SURAKARTA - Ariyadi, Supri; ., Rusnaini; Muchtarom, Moh. (Educitizen, 2017)
The objective of research was to find out: (1) how the implementation of tolerance values internalization was by Forum Persaudaraan Bangsa Indonesia (FPBI) in Surakarta City, (2) what constraints Forum Persaudaraan Bangsa Indonesia (FPBI) in Surakarta City faced in implementation of tolerance values internalization in Surakarta City, and (3) how the effect of tolerance values internalization was on the improvement of social integration in Surakarta City. The internalization of tolerance values carried out by FPBI of Surakarta city exerted effect on the people?s tolerance attitude, despite not too considerable effect. However, the people who had attended the tolerance values internalization activity held by FPBI, the one in Kampung Baru, Pasar Kliwon Subdistrict, of Surakarta, had become more tolerant and appreciating the difference, thereby leading to the improvement of social integration, manifested in harmonious interaction among the people, the existence of social activity, and the cooperation between the people with different ethnical and religious background. KATA KUNCI: Internalisasi nilai toleransi, integrasi sosial.